Perancangan Sistem Pengelolaan Data Untuk Mendukung Kinerja Kemahasiswaan Pada Universitas Atma Jaya Makassar - Pranscilia Siada; Astrid Lestari Tungadi (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
BKAM had difficulty in reporting to SIMKATMAWA, in finding data on achievements and student activities that had been carried out. The purpose of this study is to design a student activity management system to support the performance of the UAJM student bureau and design the UAJM student data structure to fit the SIMKATMAWA. The author understands the scope of the ranking, some data from SIMKATMAWA will be used as needed in UAJM student activities that have not been well recorded. Student performance data management system designed for data management that helps collect data, manage and present useful data for SIMKATMAWA, in support of student data needs within the UAJM student body. The results of the research make it easy for student affairs bureaus to get information on student activities, so that the data can be used for SIMKATMAWA reporting purposes.